2017
DOI: 10.1371/journal.pone.0178742
|View full text |Cite
|
Sign up to set email alerts
|

Association among presence of cancer pain, inadequate pain control, and psychotropic drug use

Abstract: IntroductionPain is a common symptom in cancer patients, and its control and management are complex. Despite the high concomitant use of psychotropic drugs among such patients, the association among pain, inadequate pain control, and psychotropic drug use has not been fully determined. This study examined the prevalence of cancer pain and inadequate pain control and the association with psychotropic drug use.Materials and methodsIn this cross-sectional study, we investigated 402 medical records obtained by sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…On occasion, pharmacological treatments for pain and anxiety can be the same. However, despite the fact that the WHO, the American Cancer Society, and the European Society for Medical Oncology [11,19,20] include the use of psychotropic drugs in their guidelines on the management of oncological pain, consumption of these is not always related with greater pain control in patients with cancer [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On occasion, pharmacological treatments for pain and anxiety can be the same. However, despite the fact that the WHO, the American Cancer Society, and the European Society for Medical Oncology [11,19,20] include the use of psychotropic drugs in their guidelines on the management of oncological pain, consumption of these is not always related with greater pain control in patients with cancer [4].…”
Section: Discussionmentioning
confidence: 99%
“…The Globocan 2018 database reported 18.1 million new cases in the year 2012, estimating that, in 2040, this will increase to 29.5 million new cancer diagnoses worldwide [3]. The complexity of the oncological process, the diagnosis, treatment, secondary effects, and pain, among other aspects, are all associated with greater emotional distress [4].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of pain were significantly related to psychotropic medication use. Similar studies support this finding with users of psychotropic drugs reporting poor pain control [42,43]. Helstrom and colleagues (2018) found that chronic pain was identified in 14% of 250 older adults who were recently prescribed a psychotropic medication, who also reported pain interference with daily activities [44].…”
Section: Discussionmentioning
confidence: 72%
“…Although the adequacy of analgesic medications has gradually improved over time with the recommendation of the WHO three-step ladder approach, approximately 25% of patients with cancer pain remain undertreated [11,12]. In addition to the complicated and multifactorial mechanisms of cancer pain, the challenges involve both patients' and healthcare professionals' concerns about opioid addiction and the side efects of long-term analgesic treatment [13].…”
Section: Introductionmentioning
confidence: 99%